Waste less time on Facebook — follow Brilliant.
×

anyone can help me?

\( \frac{3}{x}-\frac{4}{y}+\frac{6}{z}=1 \)

\( \frac{9}{x}+\frac{8}{y}-\frac{12}{z}=3 \)

\( \frac{9}{x}-\frac{4}{y}+\frac{12}{z}=4 \)

x=?

y?

z?

thank you.. :)

Note by Juang Bhakti Hastyadi
3 years, 8 months ago

No vote yet
1 vote

Comments

Sort by:

Top Newest

Let \(\frac{1}{x}=X,\frac{1}{y}=Y,\frac{1}{z}=Z\)

As such, the system of equations will be reduced to

\[\begin{align*} 3X-4Y+6Z &=1 \\ 9X+8Y-12Z &=3 \\ 9X-4Y+12Z &=4 \end{align*}\]

Solving them gives us

\[X=\frac{1}{3},Y=\frac{1}{4},Z=\frac{1}{6}\]

\[\therefore x=3,y=4,z=6\] Ho Wei Haw · 3 years, 8 months ago

Log in to reply

×

Problem Loading...

Note Loading...

Set Loading...